Levels of mental health problems among UK emergency ambulance workers. Issue 2 (26th February 2004) - Bennett, P; Williams, Y; Page, N; Hood, K; Woollard, M
Abstract : This study examined the prevalence of post-traumatic stress disorder (PTSD), depression, and anxiety in a sample of emergency ambulance personnel. Of 1029 personnel in one ambulance service mailed a questionnaire, 617 were returned. Among respondents, the overall rate of PTSD was 22%. Levels of PTSD did not differ according to grade, but men had a higher prevalence rate than women (23% compared with 15%). Nearly one in ten reported probable clinical levels of depression, 22% reported probable clinical levels of anxiety based on Hospital Anxiety and Depression Scale scores.